Encyclopedia of Seaplanes and Flying Boats - Clanton, Miah, author 648229 (Delhi, India : Learning Press : World Technologies, 2012)
Grumman G-111 Albatross amphibious flying boar of Chalks International Airlines landing in Miami Harbor in March 1987. A sea plane is a fixed-wing aircraft capable of taking off and landing (alighting) on water. Seaplanes which can also take-off and land on airfields are a small subclass called amphibian aircraft. Seaplanes and amphibians are usually divided into two categories based on their technological characteristics: floatplanes and flying boats, which are generally far larger and can carry far more. These aircraft were sometimes called hydroplanes. The word "seaplane" is used to describe two types of air/water vehicles: the floatplane and the flying boat. A floatplane has slender pontoons, or floats, mounted under the fuselage. Two floats are common, but other configurations are possible. Only the "floats" of a floatplane normally come into contact with water. The fuselage remains above water. Some small land aircraft can be modified to become float planes and in general floatplanes are small aircraft. Floatplanes are limited by their ability to handle wave heights typically greater than 12 inches (0.31 m). These floats add to the empty weight of the airplane, and to the drag coefficient, resulting in reduced payload capacity, slower rate-of-climb and slower cruise speed.